Pengaruh Aromatherapy Peppermint Terhadap Frekuensi Mual Pada Ibu Hamil Trimester I Di Puskesmas Serpong I: The Effect of Peppermint Aromatherapy on the Frequency of Nausea in Pregnant Women in the First Trimester at the Serpong I Community Health Center - Ilmiah To Rahmah, Ulfa (Dohara POAJ, 2024)
Introduction: Morning sickness is a natural symptom and often occurs in the first trimester of pregnancy in the form of complaints of nausea and vomiting. Nausea usually occurs in the morning but can occur at any time and at night. The incidence of nausea and vomiting in Indonesia is around 10% of pregnant women affected by emesis gravidarum, while the incidence of hyperemesis gravidarum in Banten province reaches 57,429 (24.5%) of 222,789 pregnant women. This study aims to determine the effect of giving peppermint aromatherapy to reducing the frequency of nausea in pregnant women in the first trimester at the Serpong 1 Health Center in 2023. Methods: This study used the Quasi-Experimental designs method with pre-test and post-test without a control group. The sampling technique used is total sampling with a total sample of 22 respondents. Results: The results of the research showed that there was an effect of using peppermint aromatherapy on reducing the frequency of nausea in first-trimester pregnant women based on the Wilcoxon statistical test results obtained p-value 0,004 < 0,005. Discussion: This study concludes that there is an effect of using peppermint aromatherapy on reducing the frequency of nausea in first-trimester pregnant women at the Serpong I Public Health Center in 2023. Suggestions for pregnant women to be able to increase their knowledge and understanding regarding the use of peppermint aromatherapy as a complementary treatment for nausea in the first trimester of pregnancy so that the incidence of nausea and vomiting in pregnant women in the first trimester can be resolved properly.